Intersexo e Identidade: História de um corpo reconstruído - Lima, Shirley Acioly Monteiro de (2007)
Intersex and identity: history of a reconstructed body is a Social Psychology study on the issue of the intersex identity and focuses on the process of reconstruction of self of a individual that had collated with situations that implied in the revision of its individuality, social identity and conscience of itself . Its hypothesis is of that the fight of the intersex people represents the attempt to exceed the stigma of a biological load interpreted as problematic and to establish a more favorable relation with the social environment. These individuals search to define a new social space and to conquer autonomy on its lives; they want to leave the confinement imposed for the shame and isolation which they are submitted and to be able to decide who they are. To answer to the research question - and considering the gap in national studies referring to the study of subjectivity in the intersexuality - I used as methodology of study the narrative of life history of a person diagnosed with genital ambiguity to allow the understanding of the process of social reconstruction of its body since, to change a body, to agree or not with the social demands should be in accord with the intentions, initiatives and pretensions of the person that recognizes her/himself (or not) in its alive body, once this body is organic substratum in which the personal existence incarnates